Synopsis, Productivity and efficiency of smallholder teff farmers in Ethiopia - Bachewe, Fantu Nisrane; Koru, Bethlehem; Taffesse, Alemayehu Seyoum (International Food Policy Research Institute, 2015)
A large proportion of Ethiopians derive their livelihoods from smallholder agriculture. This has provided the impetus for the smallholder agriculture-focused policies that have guided agricultural development efforts in Ethiopia over the past two decades. In this study, we investigate the productivity of smallholder teff farmers in Ethiopia, since this is an important crop in terms of cultivated area, food expenditure, and gross domestic product. Despite the remarkable growth in the production of teff in the last decade, the drivers of this growth are not well understood. In particular, there is a lack of evidence on the contribution of improvements in productivity to this growth and the link between farm size and productivity. This study employs data envelopment analysis on a recently collected large farm household survey dataset from Ethiopia to measure relative productivity and efficiency of teff farmers and to identify the factors that explain differences in relative productivity and efficiency.